Effect of Different Feed Restrictions on Growth, Biometric, and Hematological Response of Juvenile Red Tilapia (Oreochromis spp) - Adam Robisalmi; Kartiawati Alipin; Bambang Gunadi (Jurnal Ilmiah Perikanan dan Kelautan, 2021)
Highlight ResearchThere has been a significant decrease in growth, condition factors, hepatosomatic index along viscerosomatic index with the length of time for feed restriction, although fasting for up to 28 days did not cause fish mortalityHematological parameters such as RBCs, WBCs, hematocrit, and hemoglobin decreased significantly, but after re-feeding increased significantly in consecutive timesThe blood glucose levels decreased during feed restriction and gradually increased after re-feedingFeed restriction ï¬sh gained weight continuously during re-feeding, but no displaying compensatory growthThe decrease in hematological parameters did not indicate stress levels in fish, but reflected a lack of nutrition condition AbstractThe management of red tilapia culture can be improved through restriction of feed. This study aimed to determine the impact of feed restriction time and re-feeding on the growth and hematological performance of juvenile red tilapia. This study used an experimental method with a completely randomized design consisting of five treatments with four replications, namely the fish were given food for 28 days (A), 7 days of feed restriction followed by 21 days of refeeding (B), 14 days of feed restriction followed by 14 days of refeeding (C), 21 days of feed restriction followed by 7 days of refeeding (D) and 28 days of feed restriction (E). The parameters observed were growth, biometry, and hematological values. The results showed that during the feed restriction period there was a significant decrease in growth, condition factors, hepatosomatic index along with viscerosomatic index with the length of time for feed restriction, although fasting for up to 28 days did not cause fish mortality. Hematological parameters such as RBCs, WBCs, hematocrit, and hemoglobin decreased significantly, but after re-feeding, they increased significantly in consecutive times. As for the blood glucose levels decreased during feed restriction and gradually increased after re-feeding. This study stated that feed restriction ï¬sh gained weight continuously during re-feeding, but no displaying compensatory growth. The results suggested that the decrease in hematological parameters did not indicate stress levels in fish, but reflected a lack of nutrition condition.